Carotenoid profiles of red- and yellow-colored arils of cultivars of Taxus baccata L. and Taxus × media Rehder. (June 2021) - Schex, Roland; Lieb, Veronika M.; Schäfer, Christian; Schweiggert, Ralf; Steingass, Christof B.
Abstract: The botanical delimitation of Taxus species and cultivars may be facilitated by characterizing the pigment profiles of their red- and yellow-fleshed arils. Therefore, we determined genuine carotenoid profiles of differently colored arils of seven defined cultivars of Taxus baccata L. and Taxus  ×  media Rehder. In-depth HPLC-DAD-ESI/APCI-MS n analyses revealed the presence of 43 carotenoids. Exceptional retro -carotenoids dominated the profiles of all samples assessed. Rhodoxanthin ( E/Z )-isomers were predominant in the red-colored arils, resulting in a rather unusual abundance of carotenoid isomers as expressed by ratios of up to 1.3:2.0:0.9 between (all- E )-, (6 Z )-, and (6 Z, 6′ Z )-rhodoxanthin, respectively. By contrast, the uncommon yellow arils of Taxus baccata L. 'Lutea' mainly contained eschscholtzxanthin ( E/Z )-isomers and esters. Total carotenoid concentrations ranged from 17.00 to 58.78 μg/g fresh weight across all samples assessed. Highest total rhodoxanthin concentrations of 51.33 ± 0.46 μg/g fresh weight were obtained from the red arils of Taxus × media Rehder 'Hicksii'. Overall, Taxus arils represent a promising source of carotenoids and, in particular, of retro -carotenoids with exceptional molecular structures and extraordinary absorption properties. Graphical abstract: Image 1 Highlights: A total of 43 carotenoids was identified in Taxus arils by HPLC-DAD-ESI/APCI-MS n . Genuine carotenoid profiles of yew arils were dominated by unusual retro -carotenoids. Eschscholtzxanthin is the major pigment in the yellow arils of T. baccata 'Lutea'. Carotenoids were quantitated in arils of seven T. baccata and T.  ×  media cultivars. Rhodoxanthin concentrations were highest in the red arils of T.  ×  media 'Hicksii'.